ANALISIS PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PT. AMERICAN PRESIDENT LINE INDONESIA (PT APL INDONESIA) - Joonner Rambe dan Mayang Prisma Tami (Fakultas Ekonomi Universitas Borobudur, 2016)
The data used in this study in the form of primary data collected from respondents' answers based on questionnaires given, ie as many as 80 people. In addition, data on competency policy, motivation, employee performance and other literature studies. The method of data processing using multiple linear regression analysis method with the aid of SPSS version 19. Statistical test using individual significance test (t test) and simultaneous significance test (F test).The results showed that simultaneously competence and motivation variables significantly influence employee performance. Partially shows that in the analysis of competence have a positive and significant effect on employee performance, so also in motivation analysis showed significant influence to employee performance.From the analysis of data obtained the results of multiple regression equation as follows, Y = 10.382 + 0.310X1 + 0.480X2, this equation explains that competence has a positive and significant relationship to employee performance. Similarly, the motivation that has a form of positive and significant relationship to employee performance. Furthermore, it is found that the relationship between competence and motivation on employee performance has a form of positive relationship, very strong, direct and significant. From the research also found that the value of determination is equal to 76.70% changes in employee performance is influenced by the competence and motivation together and the remaining 23.3% influenced by other variables not examined. Keywords : Competence and Motivation to Employee Performance